Analysis Of Cyberloafing Behavior Restriction Strategies At Company X - Haekal Fikri Safdeni; Christian Wiradendi Wolor; Marsofiyati, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study examines restriction strategies to manage cyberloafing behavior in Company X, a public transportation organization grappling with productivity issues due to excessive non-work-related internet usage by employees. Employing a qualitative case study approach, the research collected data through in-depth interviews, observations, and document reviews. Findings indicate that while cyberloafing may offer temporary stress relief, it adversely impacts employee productivity, task completion, and team cohesion. The research highlights the effectiveness of selective restriction strategies, such as limiting non-essential internet access, implementing a reward and punishment system, and fostering a supportive work environment. Moreover, ergonomic office designs and employee training on time management are essential to sustain productivity and minimize distractions. These insights provide practical recommendations for organizations to implement balanced restriction strategies that promote both employee satisfaction and workplace efficiency.